Correlation between qualitative indicators of Holstein sire’s semen - Shamshidin, Alzhan; Alshinbaev, Orinbasar; Mussabekov, Aidos (Scientific Journal of Zoology, 2017)
The differences of sperm performance parameters of sires related to their age and determined, regression analysis between the main quantitative and qualitative indicators of sperm performance of bulls of high producing dairy breeds and indicators of sperm was carried out. Analysis of indicators of sperm performance of sires of Holstein breed showed that with age the average volume of semen increased by 19 %, sperm motility by 1.3 %, concentration of sex cells by 8.7 %, amount of semen doses obtained 25 %, and the number of rejected semen doses decreased by 8.0 %. Also with the age parameters of bulls’ sex cells increased by 17 %, resistance by 4.7 %, survival of spermatozoa by 11.5 %.